Family Socioeconomic Status and Internalizing Problem Behavior Among Chinese Adolescents: The Chain Mediation Effect of Academic Performance and Peer Conflict - Wang, Yangyang; Xie, Tian; Xu, Jian (Frontiers in Psychology, 2022)
This study aims to provide a new perspective on the relationship between family socioeconomic status (SES) and internalizing problem behavior (IPB) among adolescents. Many studies have focused on the relationship between family SES and IPB among adolescents; however, research on the underlying mechanism is still insufficient, and peer conflict has been ignored as a crucial social relationship factor for adolescents. This study identifies two new mediating variables and a chain mediating mechanism model between them. Using national longitudinal data from 2,467 adolescents aged 10–15 published in the China Family Panel Studies of wave 2018, this study found the following: (1) higher family SES can significantly reduce peer conflict and IPB among adolescents; (2) adolescents with better academic performance were less likely to be involved in peer conflict; (3) peer conflict mediated 30.41% of the relationship between family SES and adolescent’s IPB; and (4) there was a chain mediating mechanism, and the mediating effect of peer conflict was much stronger than the mediating effect of both academic performance and the chain mediation pathways. This is the first study to develop a chain mediation model to examine the roles of academic achievement and peer conflict in the relationship between family SES and IPB. These findings are significant in that they highlight the importance of providing adolescents with proper emotional de-escalation and peer conflict resolution strategies, contributing to the management of adolescent mental health in urban governance and rural development.